Legume Wafer Supplementation to Increase the Performance of Post-Weaning Ettawa Grade Goats - Brilian Desca Dianingtyas; Yuli Retnani; Dwierra Evvyernie (Media Peternakan, 2017)
This research was conducted to analyze the effect of legume wafer supplementation on the performance of post weaning Ettawa Grade goats. A total of 16 post weaning Ettawa Grade goats (average body weight 13.10±0.91 kg) were grouped into 4 group treatments and 4 blocks as replicate in a completely randomized block design. The treatments were T0 (basal diet/control), T1 (supplementation of 12.12% wafer supplement of Indigofera zollingeriana), T2 (supplementation of 13.54% wafer supplement of Leucaena leucocephala) and T3 (supplementation of 12.37% wafer supplement of Calliandra calothyrsus). The feed intake, nutrient digestibility, average daily gain (ADG), feed efficiency (FE), and income over feed cost (IOFC) were observed. The results showed that supplementation of legume wafer increased (P<0.05) the feed intake, organic matter digestibility, ADG, FE, and IOFC. Supplementation of I. zollingeriana wafer increased ADG by 55.08%, FE by 34.91%, and IOFC by 14.53%; L. leucocephala wafer increased ADG by 66.18%, FE by 41.63%, and IOFC by 19.09%; and C. calothyrsus wafer increased ADG by 32.62%, FE by 11.30%, and IOFC by 14.34%. In conclusion, the addition of legume wafer supplements into the rations could increase the feed utility value of legumes and L. leucocephala wafer at 13.54% showed the best performance in post-weaning Ettawa Grade goats.